Forensic Nursing State of the Science: Research and Practice Opportunities. Issue 1 (January 2018) - Drake, Stacy A.; Koetting, Cathy; Thimsen, Kathi; Downing, Nancy; Porta, Carolyn; Hardy, Peggy; Valentine, Julie L.; Finn, Cris; Engebretson, Joan
ABSTRACT: Introduction: The International Association of Forensic Nurses (IAFN) is the only nursing organization advancing the forensic nursing specialty. The organization seeks to advance the profession, and one mechanism for doing so is development of a research agenda. Methods: The purpose of this action-based research study was to aid in the development of a forensic nursing research agenda. The study was carried out in two integral stages: (a) focus groups with IAFN members attending the annual conference and (b) reviewing posted IAFN member listserv material. Results: The findings of this study identified similar gaps of other nursing specialties experiencing "growing pains, " including role confusion and variation in educational preparation. Conclusion: Findings from this study will inform development of the IAFN 5-year research agenda to advance forensic nursing science and evidence-based practice.